The life satisfaction of Polish nurses at the retirement age = Satysfakcja z życia pielęgnairek w wieku emerytalnym - Agata Pietraszek; Marianna Charzyńska-Gula; Beata Dobrowolska; Andrzej Stanisławek; Marta Łuczyk (Kazimierz Wielki University, 2016)
Pietraszek Agata, Charzyńska-Gula Marianna, Dobrowolska Beata, Stanisławek Andrzej, Łuczyk Marta. The life satisfaction of Polish nurses at the retirement age = Satysfakcja z życia pielęgnairek w wieku emerytalnym. Journal of Education, Health and Sport. 2016;6(9):333-344. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61885 http://ojs.ukw.edu.pl/index.php/johs/article/view/3806 https://pbn.nauka.gov.pl/sedno-webapp/works/746747       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016.     The life satisfaction of Polish nurses at the retirement age Satysfakcja z życia pielęgnairek w wieku emerytalnym   Agata Pietraszek1, Marianna Charzyńska-Gula2, Beata Dobrowolska3, Andrzej Stanisławek1, Marta Łuczyk1     • Chair of Oncology and Environmental Health, Faculty of Health Sciences, Medical University of Lublin, Poland • Faculty of Social Sciences and Humanities, Higher Vocational School Memorial of Prof. Stanislaw Tarnowski in Tarnobrzeg, Poland • Chair of Development in Nursing. Faculty of Health Sciences, Medical University of Lublin, Poland     Corresponding author: AgataPietraszek, Chair of Oncology and Community Health Care, Medical University of Lublin; StanisławaStaszica4/6 (Collegium Maximum), 20-081 Lublin, Poland; telephone: +48 609456804; fax: +48 81 4486811  email: krzos.agata@gmail.com, agata.pietraszek.umlub@gmail.com     Abstract Background: Research on the life satisfaction of nurses at the retirement age can help identify elements which have an impact on this aspect of the quality of nurses' life. In spite of the number of studies available in the field there is still no consistent data regarding the issue of life satisfaction among nurses at this stage of life.The aim of the study was to explore chosen factors associated with the life satisfaction of Polish nurses at the retirement age. Methods: A quantitative approach was adopted. Data was collected using a survey questionnaire to be completed by 135 nurses (100%) at the retirement age from seven randomly chosen District Chambers of Nurses and Midwives in Poland. Two research tools were used: a questionnaire developed by the authors and the Satisfaction With Life Scale (SWLS) by E. Diener. The collected data was analysed using  STATISTICA version 10.0. Results:  Statistically significant variables affecting the level of life satisfaction included the type of professional activity, type of workplace and managerial functions served, and also affiliation with a given District Chamber of Nurses and Midwives. There was no significant correlation between the level of life satisfaction and the level of job satisfaction among the nurses surveyed. Conclusions: A correlation was identified between some elements of professional activity and the life satisfaction of nurses at the retirement age. This should be taken into account when considering different aspects of the organisation of nurses' work. In the light of the changes of retirement schemes across the world a broader discussion is needed regarding the issue of the life satisfaction of nurses at the retirement age in order to study the possible correlations between their professional activity and satisfaction with life. Developing a clear strategy for planning the forms of activation of retired nurses and using their potential and experience in the healthcare system is recommended, especially given the situation of nurses shortage.  Key words: Ageing,  Job satisfaction, Nurses, Personal satisfaction, Poland, Retirement